A Revolution in Movement : Dancers, Painters, and the Image of Modern Mexico - Snow, K. Mitchell (Book collections on Project MUSE., 2020)
"This book illuminates how collaborations between dancers and painters shaped Mexico's postrevolutionary cultural identity, tracing this relationship throughout nearly half a century of developments in Mexican dance from the 1920s to the 1960s"--